The historiography of the village community in medieval law - Eldridge, L (2021)
This thesis explores the English medieval village community as both a lived historical reality and as a legal historical concept. It traces the study of the village community from the historical studies in the early nineteenth century, and through to current research on the topic. It does so in order to make the following claims: first, the village community remains an interesting and valuable object of legal historical study in demonstrating a ‘bottom-up’ notion of law, despite having fallen out of favour; secondly, the early scholarship still has some interesting concepts to offer in the form of a focus on community-led decision making and its role in the early common law, despite many of its premises being disproved in the intervening one-hundred-and-fifty years; thirdly, a definitional framework other than legal positivism, which does not accommodate concepts emerging from custom unless and until they are given the authoritative weight of a sovereign authority, is required in order to describe these customary law concepts. This partly explains why today’s legal theory, often dominated by legal positivism, does not tend to engage with customary law, but doing so is a valuable enterprise as one of many enlightening models of law. A detailed consideration of the substantive customary laws of village communities demonstrates alternative ways of making and conceiving of law not dependent directly on state authority, and property rights not focused on individualistic aims. It engages in a discussion as to whether medieval customary law ought to be considered ‘law’, concluding in favour and arguing that this enables a more fulsome consideration of the English medieval legal landscape.